“Yamskaya Sloboda” by Andrei Platonov: Topoi of the Steppe (Филологический класс, 2021)
The paper investigates the symbolic-semantic content of the spatial ideas of Andrei Platonov formulated in his novel “Yamskaya Sloboda” (1927). The aim of the study is to assess the semantic significance of the image of the steppe associated with the inner life of the characters, based on modern interpretations of the concepts of “topos” and “locus”. The paper looks at the dialogical interaction between poetic and philosophical forms of thinking, which makes up the basis of the author’s style. The artistic world of the novel is interpreted on the basis of the diachronic principles of historical poetics. The study analyzes the personage of Filat and the main topoi of the story: “steppe”, “steppe people”, “humble person” , and “return to his native place”. The suggested method of analysis allows to identify stable mythopoetic and autointertextual configurations of the spatial worldview. The interpretation of the “Yamskaya Sloboda” in the light of the phenomenology of space convinces that intense micro-topoi, topoi-situations, and rhetorical figures serve as impulses for the development of Platonov’s individual toposphere associated with national consciousness. The topoi of the steppe organize the plot structure of the story. They outline the possibility of restoring the social and natural unity of man. The reproduction of the whole (connection between the physical and spiritual) in its parts (characters, images of nature and everyday scenes) became the dominant law of composition and semantic form of the “Yamskaya Sloboda”. The connection between the individual properties of the soul of the protagonist of the novel and the value-based foundations of popular-historical existence characterizes the originality of Platonov’s artistic space. The novel actualizes the national topic: a centuries-old stock of motifs, plots, and mythologemes. With the help of the topoi of the steppe, Platonov translates events, images of memory, and phenomena of collective consciousness into an ideological and philosophical plan, considering the inner world of a person to be its center.